Morphological changes of lenticels and their role in gas exchange and sprouting physiology of potato tubers during postharvest storage - Magwaza, Lembe S.; Bernal, Antonio J. B.; Chope, Gemma A.; Alamar, M. Carmen; Terry, Leon A. (Frontiers in Plant Science, 2025)
The application of exogenous gases has been used to suppress sprouting in stored potato tubers. However, their efficacy in extending ecodormancy largely depends on achieving optimal gas exchange between the storage atmosphere and the tuber itself. This study aimed to investigate morphological variations and spatial distribution of lenticels and apical buds and to identify their potential role in tuber respiration rate and sprouting of five potato cultivars (‘Hermes’, ‘Lady Claire’, ‘Lady Rosetta’, ‘Saturna’, and ‘VR808’) during storage. Results revealed a consistent spatial pattern wherein the apical section of potato tubers exhibited significantly higher bud counts compared to lateral and stolon regions. ‘Lady Claire’ stood out as having the highest number of apical buds among the cultivars studied. Digital image analysis showed a seven times higher number of buds surrounding the apical eye and these were generally smaller than those distributed across the skin. ‘Saturna’ displayed double the lenticel density (12 lenticels cm-2) in smaller tubers, suggesting an inverse relationship between tuber size and lenticel density. ‘Lady Claire’ and ‘Saturna’ had respiration rates of 2.75 and 1.9 mL CO2 kg-1 h-1, respectively, and were selected for additional respiration and ethylene efflux analyses. In both cultivars, distinct spatial differences were observed, with the apical section exhibiting a seven-fold increase in lenticel density compared to the lateral and stolon sections. Respiration rate increased five-fold when apical lenticels were blocked, whereas it decreased 30-fold when the apical was the only unblocked section, suggesting differential physiological activity across lenticel locations. The apical sections, with the highest lenticel density, exhibited elevated respiration rates as a stress-induced physiological response upon blockage, compared to the lateral and stolon sections. Lenticels changed their morphology during storage, erupting before bud movement, suggesting lenticel eruption could be used as a pre-symptomatic visual marker of dormancy break. This study highlights the critical role that lenticel morphology and spatial distribution may have in determining potato tuber gas exchange and refining allied storage regimes.